A scanner darkly - Dick, Philip K. (Mariner Books/Houghton Mifflin Harcourt, 2011)
Set in suburban Orange County, California in a future where America has lost the war on drugs. When one reluctant undercover cop is ordered to start spying on his friends, he is launched on a paranoid journey into the absurd, where identities and loyalties are impossible to decode. Based on the experiences of the author, Philip K. Dick.